Understanding cross-cultural management - Browaeys, Marie-Joelle; Price, Roger, 1946- (Financial Times/Prentice Hall, 2011)
Offers a selective but broad view of classic and contemporary thinking on cultural management, and encourages you to apply theories and ideas to practice and to relate them to your own experience. This is achieved through varous examples and cases from the business world, and a range of practical activities.